Determination of Critical Organ Effective Dose in Head CT Scan Examination at Bali Mandara Hospital - Gusti Ngurah Sutapa; Winer Johan Bora; I Gde Antha Kasmawan; Ni Kadek Nova Anggarani; I Ketut Putra; Ni Putu Yuni Nurmalasari (Universitas Hamzanwadi, 2025)
The study aims to determine the effective dose to critical organs in head CT scans at RSUD Bali Mandara and analyse the difference in effective dose between male and female patients and compare it with BAPETEN's normal threshold. Secondary data including current, voltage, CTDIvol, and DLP were collected and grouped by gender. The effective dose was calculated by multiplying DLP by the conversion factor K and CTDIvol by the organ weight factor (WT). The mean effective dose of male patients was 4.35 ± 0.68 mGy, while that of female patients was 4.00 ± 0.53 mGy. The effective dose of critical organs for males was 0.642 mGy and for females 0.613 mGy, with higher doses for males. Statistical analysis using t-test shows the value of tcount < ttable, which indicates that the effective dose in head CT scan examination at RSUD Bali Mandara is still within normal limits according to the BAPETEN DRL standard Number: 1211/K/V/2021.